5x+6-2=-5-x

Simple and best practice solution for 5x+6-2=-5-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6-2=-5-x equation:



5x+6-2=-5-x
We move all terms to the left:
5x+6-2-(-5-x)=0
We add all the numbers together, and all the variables
5x-(-1x-5)+6-2=0
We add all the numbers together, and all the variables
5x-(-1x-5)+4=0
We get rid of parentheses
5x+1x+5+4=0
We add all the numbers together, and all the variables
6x+9=0
We move all terms containing x to the left, all other terms to the right
6x=-9
x=-9/6
x=-1+1/2

See similar equations:

| 0.62+0.18t=1.34t-1.12 | | 0.12(y-6)+0.16y=0.08y-0.05(20) | | 3(x-2)=6x+12 | | -14=x/4-10 | | 8(n-3)-2(n-9)=3n+8+n | | 34=2(2x)+2(x-4) | | -6+x/7=-9 | | 4m^2-6=58 | | a+4/8=2 | | -9=-1+x/3 | | 2x-4+4x=2x+12 | | 2(x-6)+4=8(1/2x-4) | | 164=2(x+15)+2x | | 30-48v+12=54 | | X+1.5(x-3)=5/2 | | -7.3+x/9.2=-0.739 | | (1x+2)*(2x+1)=252 | | 1÷3x+4=x-2 | | x+2x-7=510 | | (x+1)/5=9/10 | | 1/6(x-5)=1/2(x+6) | | 2x-2x-7=510 | | 3q+9=27 | | x2-8x=0 | | 4n-8n=4 | | X-5y=50 | | 15y+18y=102 | | -42=-3n-3 | | -5x+11=46 | | y/3=19.2 | | -3/4+4/3x=-7/2 | | x2-7x+6=0 |

Equations solver categories